Web3: Unleashing the Power of Decentralization and Blockchain Technology to Transform the Digital Landscape - Peddaeluka Teja Simha Reddy,S Venkata Achuta Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The research paper explores the concept of Web3, its implications for decentralization, user ownership, and empowerment. The paper provides an in-depth analysis of Web3's impact on data ownership, privacy, and user control. It examines the role of blockchain technology and decentralized applications (DApps) in enabling a more decentralized internet ecosystem. The research highlights the contrasts between Web 2.0 and Web3, emphasizing the shift towards user-centricity and increased user empowerment. Challenges and considerations in Web3 adoption are discussed, along with future perspectives and potential applications in various industries.